Pentingnya mitigasi risiko pembiayaan murabahah bank syariah - Khotimah, Khusnul (Maliki Interdisciplinary Journal, 2023)
In reality the risk is not expected, but the risk is possible. From this it indicates the need for the implementation of risk management. One of the stages of risk management is mitigation or control. This mitigation stage is important for the risk of murabahah financing in Islamic banks. The reason is that murabahah financing is the most widely used financing by Indonesian customers. This study aims to determine how important the risk mitigation stages of murabahah contract financing are. The method used is literature study. This research begins with the collection of data, then it is read, recorded and processed which becomes the research material. The results obtained from this study are that the mitigation or control stage is important because management needs to ensure that management and the risk management model can be carried out according to plan. In addition, management also monitors any trend of risk changes, due to the nature of risks that can develop.